2022
DOI: 10.3390/ijms24010039
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Concentrate in the Diet of Early Lactation Dairy Cows Has Contrasting Effects on Circulating Leukocyte Global Transcriptomic Profiles, Health and Fertility According to Parity

Abstract: The functionality of circulating leukocytes in dairy cows is suppressed after calving, with negative energy balance as a risk factor. Leukocyte transcriptomic profiles were compared separately in 44 multiparous (MP) and 18 primiparous (PP) Holstein–Friesian cows receiving diets differing in concentrate proportion to test whether immune dysfunction could be mitigated by appropriate nutrition. After calving, cows were offered either (1) low concentrate (LC); (2) medium concentrate (MC) or (3) high concentrate (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Increased values of NEFAs and BHB in the blood serum often arise in early lactation due to a decrease in feed intake when cows enter an NEB with a decrease in the glucose value [34]. Furthermore, mastitis may arise as a consequence of the NEB due to immunosuppression, but this disease can also lead to an NEB due to released cytokines that cause increased mobilization of NEFAs and consequently an increased BHB concentration in the blood serum [35,36]. On the other hand, a BHB decrease in the blood serum during the inflammation could be explained as a consequence of increased blood glucose, changes in the BHB supply via reduced rumen motility, an impairment of hepatic ketogenesis, or a combination of the aforementioned factors [37].…”
Section: Discussionmentioning
confidence: 99%
“…Increased values of NEFAs and BHB in the blood serum often arise in early lactation due to a decrease in feed intake when cows enter an NEB with a decrease in the glucose value [34]. Furthermore, mastitis may arise as a consequence of the NEB due to immunosuppression, but this disease can also lead to an NEB due to released cytokines that cause increased mobilization of NEFAs and consequently an increased BHB concentration in the blood serum [35,36]. On the other hand, a BHB decrease in the blood serum during the inflammation could be explained as a consequence of increased blood glucose, changes in the BHB supply via reduced rumen motility, an impairment of hepatic ketogenesis, or a combination of the aforementioned factors [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a situation unique to humans, i.e., industrial milk production in cows, intense and maximally prolonged lactation has an adverse effect mainly on liver function and the immune system. Cheng et al (2023) [41] demonstrated that the functionality of circulating leukocytes in dairy cows is suppressed after calving, with negative energy balance as a risk factor. Moreover, the leukocytes of multiparous and primiparous cows responded differently to the diets across age, nutrient supply, and immunity, affecting health and subsequent fertility.…”
mentioning
confidence: 99%